Influence of concrete material time-dependency and temperature on the performance of a cofferdam structure braced with braces with reinforces concrete ring beams (2017)
Asbstract: The lateral load resisting system of tall buildings is often made of reinforced concrete shear walls that are constructed using a cofferdam structure. The term cofferdam, often used in offshore applications, is employed in this research as a temporary watertight structure made of steel sheet piles and internally braced with steel or reinforced concrete ring beams to retain the surrounding soil. The soil removal inside of the cofferdam, necessary to install the foundations of the concrete core in rock or competent soil, is typically performed following a bottom-up excavation sequence. The performance of these type of systems in urban environments is critical as excessive excavation-induced ground movements can lead to significant damage of adjacent infrastructure. In this research, concrete material time-dependent and temperature-dependent effects of shrinkage, creep, and aging of concrete ring beam bracings are shown to have contributed to the lateral deformations of an urban cofferdam built for a structure that was projected as the tallest building in America. It is shown that because of the very low stiffness of perimeter steel sheet piles, the performance of these cofferdams is highly influenced by the quality control and adequate curing of the concrete material of the ring beams used as the internal lateral bracing system of the cofferdam. It is also shown with actual performance data how the sequence and timing of cycles of excavation and lateral bracing highly impacted the performance. The concrete material time-dependent effects presented in this research have not been incorporated as an integral part of the analysis and design of these temporary structures in urban environments and ignoring these effects conceal the fundamental reason for the resulting lateral deformations of these structures. Keywords: Cofferdam, bottom-up construction, field performance, concrete time-effects, concrete temperature-effects